(3QSGdI aj JMbjb QLGd CSGfjO GdCNHGQs - (3GdCUagGfj, GdeLdSj, eMeO HGbQ Hf eMeO Jbj Hf ebUhO Ydj, J (B1111 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3Efg deG GdJeS efj LeGYI ef WGdHj Ydhe CFeI GdOjf UdhGJ Gddg Ydjge CLeYjf Cf GcJH dge aj JMbjb CMhGd QLGd CSGfjO GdCNHGQ QSGdI hLjRI CbJUQ ajgG Ydi HjGf eG GJVM dj ef CMhGdge hGTJgQ YfO CUMGHfG (B...s
(3BNQgG (B:s
... (3Yf GdUOhb QFjS GdeMOKjf eMeO Hf HGHhjI QVj Gddg Yfge CLeYjf hMTQge eY GdCFeI GdWGgQjf hef gPG GdSfO jXgQ WQjK CjVG Edi SGFQ GdcJH GdCQHYI (B.. (3NJefG GdQSGdIs
(3aQZ efgG GdeDda SfI (B: (3QLH , (B1086 (3g` aj CUagGfs
(3JHUQI GdYfhGf (B:s
(3aj GdQLGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 \48s
(3GdPQjYI (B25 \ 234s
Keywords: (3GdMOjK hGdeUWdMs